UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS 2A MI MASYHUDIYAH PADA MUATAN MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING - Alfiani Damayanti; Agung Setyawan (Program Studi PGSD, FKIP, Universitas Mataram, 2023)
This research aims to find out how the application of the contextual teaching and learning model can improve learning outcomes in mathematics content regarding sides, angles and edges of geometric shapes in class 2A MI Masyhudiyah students. This type of research is classroom action research or PTK. This research design uses the Kemmis and Mc. Taggart model which consists of 4 components, namely planning, implementing actions, observing and reflecting. The research subjects that will be used in this classroom action research are 25 students in class 2A MI Mashhudiyah, consisting of 15 male students and 10 female students. Data collection techniques in this research used interviews, observation and tests. This research data analysis technique uses quantitative descriptive. The criteria for success in this classroom action research are based on increasing student learning outcomes in each cycle. The criteria used to see the success of the action are in the form of increasing student learning outcomes. Students are declared to have improved if a minimum percentage of 70% of all students meet the KKM score of 70. The results of the research show that student learning completeness in the pre-test was 8% with an average score of 43.2%, then in cycle 1 it was 56% with an average score -an average of 68.8 and in the second cycle it was 64% with an average value of 69.2 then in the post test of third cycle it was 80% with an average value of 75. From these data it clearly shows that student learning outcomes have increased and indicators of success have been achieved